Sengketa Merek Dagang ‘Ayam Geprek Bensu’ Versus ‘I Am Geprek Bensu’ - Puspita Sari, Amelia; Fuad Wasitaatmadja , Fokky (Magister Kenotariatan, Universitas Jambi, 2026)
The trademark dispute between Ayam Geprek Bensu and I Am Geprek Bensu highlights the complexity of trademark protection in Indonesia, particularly when involving public figures and large-scale business interests. At the core of this dispute is the application of the first to file principle under Law No. 20 of 2016 on Trademarks and Geographical Indications, which affirms that legal ownership is determined by formal registration rather than prior use in commerce. This issue is not only relevant due to its controversy but also because it reflects the vulnerability of Usaha Mikro, Kecil, dan Menengah (UMKM). Many UMKM, despite operating for years, have been compelled to discontinue their brands after third parties registered them earlier. Such cases expose weaknesses in legal protection and demonstrate the limited awareness of UMKM regarding the necessity of formal trademark registration. This research employs a normative juridical method, utilizing both case study and statutory approaches to analyze the legal foundations, judicial reasoning, and consequences of applying the first to file system. Furthermore, it evaluates the extent to which Indonesia’s trademark regime influences the legal standing of UMKM and examines their capacity to safeguard business identity when competing against parties with greater resources and faster access to formal registration.